STEAP1 Knockdown Decreases the Sensitivity of Prostate Cancer Cells to Paclitaxel, Docetaxel and Cabazitaxel - Rocha, Sandra M. (2023)
FEDER funds through the POCI—COMPETE 2020—Operational Program Competitiveness and Internationalization in Axis I—Strengthening research, technological development and innovation (Project No. 029114). This work was also supported by the European Regional Development Fund through the “Programa Operacional Regional do Centro (Centro 2020)—Sistema de Apoio à Investigação Científica e Tecnológica—Programas Integrados de IC&DT” (Project Centro-01-0145-FEDER-000019—C4—Centro de Competências em Cloud Computing. Associate Laboratory Institute for Health and Bioeconomy—i4HB (project LA/P/0140/2020) which are financed by National Funds from FCT/MCTES. The microscopy facility used in the development of this work is part of the PPBI-Portuguese Platform of BioImaging and is partially supported by the Project POCI-01-0145-FEDER-022122. Publisher Copyright: © 2023 by the authors.